Efektivitas Cloud Computing dalam Manajemen Data Akademik: Tinjauan Literatur Lima Tahun Terakhir - Destriani Silla; Theresia Irnatesa Vivin; Rehan Glen Ly; Fadil Mas'ud (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Cloud computing has significantly changed how academic data is handled in higher education by making operations more efficient and effective. This review of literature from 2019 to 2024 looks at how cloud-based academic management systems are implemented, using sources like Scopus, Google Scholar, and university digital libraries. It finds out what helps these systems succeed, what problems they face, and how they affect data security and availability. The results show that having the right infrastructure, training for staff, and strong data security policies are important for success. However, challenges like cybersecurity risks and reliance on the internet are common. Cloud computing makes it easier to access data, speeds up administrative work, and helps universities move towards a more sustainable digital future. Future research should focus on improving security measures and looking into the social effects of digital education.